Histomorphological study on the ovary of neonatal Indian buffalo (Bubalus bubalis) - BHARDWAJ, R L; ROY, K S (The Indian Journal of Animal Sciences, 2014)
Histomorphological study was conducted on the ovary of 13 neonatal bufTaloes calves. The surface epithelium of the ovaries was simple cuboidal to simple columnar which was thrown into folds at locations. It was invaginated into ovarian cortex. The average height of cpithelium was 8.07±0.46 µm and thickness of tunica albuginea was 67.47±5.13 µm. The per cent distribution of cortex and mcdulla were 77.16±1.14 and 22.84±1.14 respectively. Ovarian stroma was fibrocellular struetun. It comprised mesenchymal cells difrerentiating into fibroblasts with collagen fibres and reticular fibres. No elastic fibres could be seen except at perivascular area. Smooth muscle cells were also observed. The ovarian follicles at different stages of developmcnt and atresia were observed in the ovary. Polynuclear ova were observed. The intcrstital gland cells were seen at locations. The mast cells were seen in perivascular area. The rete ovarii and mesonephric tubules were also present. They were lined with cuboidal to low columnar epithelium. Blood vessels of different caliber were seen in medulla.